Work-family enrichment as predictors of work outcomes among teachers - Hummara Akram; Najma Iqbal Malik; Masood Nadeem; Mohsin Atta (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The present study aimed at finding out work-family enrichment as predictors of work outcomes (job satisfaction, affective commitment and turnover intentions). The sample comprised of 225 individuals involved in teaching profession was selected from the public and private colleges of Sargodha. Work-Family Enrichment Scale (Carlson, Kacmar, Wayne, & Grzywacz, 2006), Minnesota Satisfaction Questionnaire (Johnson & Weiss, 1971), Affective Organizational Commitment Questionnaire (Allen & Mayer, 1990) and Turnover Intentions Scale (Vigoda-Gadot & Kapun, 2005) were used for data collection. Work-family enrichment was found as positive predictor of affective commitment and job satisfaction but negative predictor of turnover intentions. Results also showed significant differences in affective commitment and turnover intentions among employees of private and public sectors.
Keywords: 330; work-family enrichment; affective commitment; job satisfaction; turnover intentions